Acute heart failure due to giant left atrium: remote ECLS implantation for interhospital transfer and bridging to decision - El Beyrouti Hazem; Oberhoffer Martin; Kornberger Angela; Beiras-Fernandez Andres; Vahl Christian-Friedrich (Innovative Surgical Sciences, 2018)
Remote extracorporeal life support (ECLS) implantation and mobile ECLS are increasingly applied to enable the treatment of patients with refractory heart failure at specialized care centers. Giant left atrium (GLA) is a rare cause but may lead to acute and devastating heart failure.